Descriptive of Knowledge of Hypertension Preventive in Adolescents - Suci Eka Putri; Siti Maisyaroh Fitri Siregar; Adelina Irmayani Lubis; Laila Apriani Hasanah Harahap; Wardah Iskandar; Teuku Muliadi (Journal of Nutrition Science, 2022)
Hypertension is the highest cause of death in the world and one of the diseases that triggers other non-communicable diseases. There are several factors that influence the incidence of hypertension in adolescents, one of which is low knowledge about hypertension. Knowledge can influence the lifestyle of teenagers to be unhealthy. Individual actions or behavior are greatly influenced by cognitive or knowledge. The aim of this study was to see the level of knowledge about hypertension and prevention of hypertension in adolescents.The population in this study were students of Universitas Teuku Umar, with a sample of 282 respondents. The data were collected via 9-item hypertension knowledge questionnaire. The knowledge level was classified as follows: good (points average ≥18); sufficient (<18 points). The results showed that the frequency of good and sufficient levels of knowledge about hypertension was 74.5% and 25.5% each.